If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 3x + -2(x + -3) + -5 = 4(2x + -5) + 13 + -2x Reorder the terms: 9x + 3x + -2(-3 + x) + -5 = 4(2x + -5) + 13 + -2x 9x + 3x + (-3 * -2 + x * -2) + -5 = 4(2x + -5) + 13 + -2x 9x + 3x + (6 + -2x) + -5 = 4(2x + -5) + 13 + -2x Reorder the terms: 6 + -5 + 9x + 3x + -2x = 4(2x + -5) + 13 + -2x Combine like terms: 6 + -5 = 1 1 + 9x + 3x + -2x = 4(2x + -5) + 13 + -2x Combine like terms: 9x + 3x = 12x 1 + 12x + -2x = 4(2x + -5) + 13 + -2x Combine like terms: 12x + -2x = 10x 1 + 10x = 4(2x + -5) + 13 + -2x Reorder the terms: 1 + 10x = 4(-5 + 2x) + 13 + -2x 1 + 10x = (-5 * 4 + 2x * 4) + 13 + -2x 1 + 10x = (-20 + 8x) + 13 + -2x Reorder the terms: 1 + 10x = -20 + 13 + 8x + -2x Combine like terms: -20 + 13 = -7 1 + 10x = -7 + 8x + -2x Combine like terms: 8x + -2x = 6x 1 + 10x = -7 + 6x Solving 1 + 10x = -7 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 1 + 10x + -6x = -7 + 6x + -6x Combine like terms: 10x + -6x = 4x 1 + 4x = -7 + 6x + -6x Combine like terms: 6x + -6x = 0 1 + 4x = -7 + 0 1 + 4x = -7 Add '-1' to each side of the equation. 1 + -1 + 4x = -7 + -1 Combine like terms: 1 + -1 = 0 0 + 4x = -7 + -1 4x = -7 + -1 Combine like terms: -7 + -1 = -8 4x = -8 Divide each side by '4'. x = -2 Simplifying x = -2
| -5y+5=2(4y+11) | | 1/5=y/20 | | 6x+y+1=0 | | 6+5=6 | | 7-(4x-3)=6-5x | | 3/2w-(-4/5) | | 4x+11=35+x | | 3(4x+8)=-8+20 | | 3x+y-2z= | | z+1=2z-7 | | F=295-2S | | 18x-19=15+2x | | 5(x+8)=30(x-2) | | 15x^2+3x-8=0 | | 9x=342 | | X^4+5x^3+4x^2-10x-12=0 | | 4x=x^2-110 | | x+(3x)+(6x-5)=180 | | 2x-15=4x+2 | | 2(6+2x)=8 | | 4x-3+7x=30 | | -7x-3y=9findslope | | 2(5x+3)=6x-6 | | 12x^3y^2-8xy^4-9x^2y/6x^2y^2 | | 2h+6(h+3)=-14 | | K^2=50-5k | | .33x+2=19 | | 1/4x-8=5/8x | | 9=5.5+x(10.5-5.5) | | 64x^2-48x+9=(8x-3) | | n^2+12n+19=-27 | | 0.50x+0.90x=0.80 |